Wind Conditions on the Great Barrier Reef Influenced the Recruitment of Snapper (Lutjanus carponotatus) - Schlaefer, Jodie A.; Wolanski, Eric; Lambrechts, Jonathan; Kingsford, Michael J. (Frontiers in Marine Science, 2018)
Most coral reef fishes have a pelagic larval stage before recruiting to reefs. The survival of larvae and their subsequent recruitment can drive the dynamics of reef populations. Here we show that the recruitment of the snapper Lutjanus carponotatus to One Tree Island in the Capricorn Bunker Group, in the southern Great Barrier Reef, was highly variable over 23 years. We predicted that the currents in the Capricorn Bunker Group, including their wind driven components and the Capricorn Eddy (a nearby transient oceanic eddy), would affect patterns of recruitment. A biophysical model was used to investigate this prediction. L. carponotatus were collected from One Tree Island and the dates when they were in the plankton as larvae were determined from their otoliths. The winds present during the pelagic phases of the fish were examined; they were found to have survived either longshore (SSE) winds that induced little cross shelf movement in the larval plume or cross shelf (ENE) winds that induced little longshore movement. The unidirectional transportation of the larval plume in these conditions was favourable for recruitment as it kept the plume concentrated in the Capricorn Bunker Group. These winds were more prevalent in the periods of peak L. carponotatus production that preceded high recruitment. Dispersal under average winds (6.2 m s-1 from the prevailing ESE) and strong winds (velocity 1.5 times average), with and without the Capricorn Eddy, was also modelled. Each of these combinations were less favourable for recruitment than the longshore and cross shelf winds larval L. carponotatus survived before reaching OTI. The larval plume was comparatively less concentrated in the Capricorn Bunker Group under average winds. Strong winds transported the larval plume far longshore, to the NW, away from the Capricorn Bunker Group, while the Capricorn Eddy transported larvae seaward into oceanic waters. Larval swimming could counteract these dispersive forces; however, significant dispersion had occurred before larvae developed strong swimming and orientation abilities. This study provides a physical proxy for the recruitment of snapper. Further, we have demonstrated that great insights into recruitment variability can be gained through determining the specific conditions experienced by survivors.